PENGEMBANGAN SUMBER DAYA MANUSIA DALAM ORGANISASI PENDIDIKAN ISLAM - ., Kasmawati (Inspiratif Pendidikan, 2019)
Human Resources Development is very necessary because it has important aspects for increasing the productivity of Human Resources and also has certain goals which must be achieved for the progress of a company or national service organization and educational institution. Development of Human Resources can be done with training. Training conducted by social service organizations is aimed at improving the performance of Human Resources. This training is usually done according to the needs of the employees, this training is related to the management of Human Resources. According to Kett Ner there are four management functions, namely planning, organizing, actuating, and controlling. Human Resource Development is carried out through education and training, both formally and informally, which is carried out on an ongoing basis. There are five Human Resources domains that are considered important to be developed in the field of education. The five domains are: professionalism, competitive power, functional competence, participatory excellence, and cooperation. However, the development of the five HR domains requires Total Quality Control (TQC) and integrated training programs to achieve effectiveness.